The Symbols Rituals of Salako Community in Sarawak - Mangai Tugau, Mohamad Maulana Magiman, Hazizy Hanis,; Mohd Yusoff, Ahmad Nasir; Abdul Halim, Hazlina (Opción)
This research is about the symbols rituals in the culture of the Salako community in Sarawak. These symbols play a vital role, especially their rituals that serve as guidance in their lives. The main focus of this research is to identify and analyse the meaning of symbols in every ritual performed. The data is collected by using an ethnographic approach in the area of Lundu and Samatan, Sarawak Besides, in-depth interviews were conducted in 2019 with indigenous leaders, cultural practitioners known as Nyangahant craftsmen, Koncong craftsmen and Sarawak state councils. The data is analysed by using the semiotic approach as a symbol used in ritual practices as unification. The findings show that the symbolism in the ritual is a self-slavery to seek the blessing of the god, which leads all the deeds in the world will bring great sustenance and bring success in all efforts. Besides, it is a concept of prosperity in the future new generation of Salako community protected from any disasters. Thus, the symbol of ritual means unity to achieve a successful life for its practitioners.